Computer network time synchronization: the network time protocol on Earth and Space - Mills, David L. (Boca Raton, FL, CRC Press, 2011)
Carefully coordinated, reliable, and accurate time synchronization is vital to a wide spectrum of fields—from air and ground traffic control, to buying and selling goods and services, to TV network programming. Ill-gotten time could even lead to the unimaginable and cause DNS caches to expire, leaving the entire Internet to implode on the root servers. Written by the original developer of the Network Time Protocol (NTP), Computer Network Time Synchronization: The Network Time Protocol on Earth and in Space, Second Edition addresses the technological infrastructure of time dissemination, distribution, and synchronization—specifically the architecture, protocols, and algorithms of the NTP. This system has been active in one form or another for almost three decades on the Internet and numerous private networks on the nether side of firewalls. Just about everything today that can be connected to a network wire has support for NTP. Evaluating historic events that have taken place since computer network timekeeping started almost three decades ago, the author details a number of systems and drivers for current radio, satellites, and telephone modem dissemination and explains how we reckon the time, according to the stars and atoms. The original 16 chapters of the first edition have been rewritten, updated, and enhanced with new material. Four new chapters cover new algorithms and previously uncovered concepts, including timekeeping in space missions. Carefully coordinated, reliable, and accurate time synchronization is vital to a wide spectrum of fields—from air and ground traffic control, to buying and selling goods and services, to TV network programming. Ill-gotten time could even lead to the unimaginable and cause DNS caches to expire, leaving the entire Internet to implode on the root servers. Written by the original developer of the Network Time Protocol (NTP), Computer Network Time Synchronization: The Network Time Protocol on Earth and in Space, Second Edition addresses the technological infrastructure of time dissemination, distribution, and synchronization—specifically the architecture, protocols, and algorithms of the NTP. This system has been active in one form or another for almost three decades on the Internet and numerous private networks on the nether side of firewalls. Just about everything today that can be connected to a network wire has support for NTP. Evaluating historic events that have taken place since computer network timekeeping started almost three decades ago, the author details a number of systems and drivers for current radio, satellites, and telephone modem dissemination and explains how we reckon the time, according to the stars and atoms. The original 16 chapters of the first edition have been rewritten, updated, and enhanced with new material. Four new chapters cover new algorithms and previously uncovered concepts, including timekeeping in space missions.